ANALISIS PERAN PEMERINTAH DESA DALAM MENINGKATKAN KOMPETENSI MASYARAKAT PADA DESA SURADITA CISAUK KABUPATEN TANGERANG - Yuniarti, Ranie; Farida, Syarifah Ida; Zulkarnain, Iskandar (SINERGI : Jurnal Riset Ilmiah, 2025)
This study focuses on the effectiveness of the Suradita Village Government, Cisauk Sub-District, Tangerang Regency, in improving community competence through household waste management training programs. This qualitative research adopts a case study approach aimed at gaining an in-depth understanding of the government’s role in community empowerment. Informants were selected using purposive sampling based on their involvement in the program, consisting of village officials, training instructors, and community participants. Data were collected through interviews, observations, and documentation, then analyzed qualitatively through the stages of data reduction, presentation, and conclusion drawing, followed by data triangulation. The findings reveal that the Suradita Village Government has effectively enhanced community competence through regular outreach activities, practical waste management training, provision of adequate facilities, and sustainable program implementation. These efforts have led to increased community awareness and skills in maintaining environmental cleanliness. The study supports Boyatzis’ competency theory, which emphasizes the improvement of individual capacity through training, and aligns with Kartasasmita’s concept of community empowerment that highlights the government’s role as a facilitator.